Iron-fueled ferroptosis: a new axis for immunomodulation to overcome cancer drug resistance—from immune microenvironment crosstalk to therapeutic translation - Wu, Yimao; Zhang, Kaiyu; Jiang, Naijun; Chen, Zichang; Sun, Xiaojing; Zha, Hongyu; Lin, Mingjun; Li, Jingxin; Pan, Xiaocheng; Chen, Jiadong; He, Junbing; Chen, Hongpeng; et al. (Frontiers in Immunology, 2026)
Resistance to chemotherapy and targeted therapy in cancer is largely due to evasion of apoptosis, but ferroptosis—an iron-dependent form of regulated cell death driven by lipid peroxidation—offers a promising alternative, particularly in aggressive and therapy-resistant subtypes. The tumor immune microenvironment plays a central role in modulating ferroptosis susceptibility: CD8+ T cell-derived IFNγ downregulates system Xc- and upregulates ACSL4, while other immune cells such as Tregs, MDSCs, and macrophages further fine-tune ferroptosis through cytokine and redox signaling. Importantly, ferroptosis induction promotes immunogenic cell death, enhancing T cell infiltration and synergizing with immune checkpoint blockade to achieve sustained antitumor immunity. This review delineates the molecular basis of ferroptosis sensitivity in resistant cancers, explores immune-ferroptosis crosstalk, evaluates combination strategies with immunotherapy, and discusses challenges such as toxicity and patient stratification to advance clinical translation.